Eyelid reconstruction after extirpation of lid tumor (Universitas Gadjah Mada, 1986)
Extirpation of eyelid benign tumor, while the vision is still good, must be followed by lid reconstruction to protect the eyeball. The means of such reconstruction to make the lid function are optimal. A case of lid reconstruction after lid benign tumor extirpation with the remain of skin and the orbicular oculi muscle has been reported. The reconstruction was carried out by replacing the lost tarsoconjunctival tissue with the opposite tarsoconjuncdval tissue. The blepharoraphy was maintained until the cicatrical tissue formation was completed. Key Words: lid tumor extirpation - reconstruction of superior levator palpebral muscle - replacement of tarsoconjunctival tissue - blepharoraphy - ophthalmic surgery